Development of the Arabic Scrabble Board Game Based on Experiential Learning as a Mufradât Learning Media - Muthmainnah, Fathimah; Ahsanuddin, Mohammad; Alfan, Muhammad (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
Interviews and observation with Arabic teachers at MTs Nurul Huda Malang showed that 56.25% of students' Arabic language scores were below KKM (score KKM [Minimum Completeness Criteria] is 74). The aim is to describe: (1) the development of the Experiential Learning-based Arabic Scrabble Board Game as a mufradât learning media for class VII students at MTs Nurul Huda, and (2) the feasibility of the Experiential Learning-based Arabic Scrabble Board Game media as mufradât learning media for class VII students MTs Nurul Huda. This uses research and development methods with ADDIE model. The research results are: (1) The production of the Arabic Scrabble Board Game consists of 6 components, and (2) The Arabic Scrabble Board Game media was tested by material expert validator with score of 100 and media expert of 97.3 (Very Good). The conclusion obtained is that the Arabic Scrabble media received the title of feasibility after validation testing by both students and trials on class VII students at MTs Nurul Huda Malang.